At Loggerheads? : Agricultural Expansion, Poverty Reduction, and Environment in the Tropical Forests. - Bank, World (World Bank policy research report., 2006)
Despite the vast number of books and reports on tropical deforestation, there's confusion about the causes of forest loss and forest poverty, and the effectiveness of policy responses. At Loggerheads seeks to describe ways to reconciles pressures for agricultural expansion in the tropics with the urgent needs for both forest conservation and poverty alleviation. It diagnoses the causes and impacts of forest loss and the reasons for the association of forests and poverty. It looks at how policies - modulated by local conditions - act simultaneously on deforestation and poverty, creating tradeof.